Fatigue Life from Sine-on-random Excitations. (2015) - Kihm, Frédéric; Halfpenny, Andrew; Ferguson, Neil S.
Abstract: This presentation concentrates on calculating the high cycle fatigue life from sine-on-random excitations. A spectral domain approach offers advantages over the time domain approach when computation times are prohibitive. The proposed approach is to derive the statistical rainflow cycle histogram from a sine-on-random spectrum of stress data and then to use the appropriate material fatigue curve to obtain the estimated life. A case study illustrates the application of the method on a component attached to a helicopter. Comparisons with traditional time-domain approaches are presented and show excellent agreement.